PENERAPAN STANDAR NASIONAL INDONESIA TERHADAP PRODUK TEKSTIL USAHA MIKRO, KECIL, DAN MENENGAH BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2008 TENTANG USAHA MIKRO, KECIL, DAN MENENGAH DIHUBUNGKAN DENGAN UNDANG-UNDANG REPUBLIK NO. 20 TAHUN 2014 TENTANG STANDA - Rai (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Implementation of the free market, especially since the Asean China Free Trade Area effectively in 2010, textile products, especially those carried out by micro, small and medium enterprises (UMKM) have become one of the sectors that have been significantly affected by competition with Chinese products. especially regarding the price. To overcome this, a standard is needed that will provide quality assurance for Indonesian domestic products and be able to increase the competitiveness of domestic products against foreign products, especially China. The quality standard label owned by Indonesia is the Indonesian National Standard (SNI), which in its application cannot be carried out optimally, especially by UMKM. The process of applying SNI to a product, especially in textile products, in practice can still be said to be a voluntary application of SNI and cannot be implemented completely by every UMKM. There are still many obstacles experienced in the application of this SNI both from within the UMKM actors and related institutions. The application of standardization which is one way of developing UMKM products in Law no. 20 of 2008 concerning MSMEs but in practice it is not appropriate, in addition to efforts to socialize SNI as stated in the Republic of Indonesia Law no. 20 of 2014 concerning Standardization and Conformity Assessment is an effort between the government and local governments in practice that cannot be carried out optimally.